2023
DOI: 10.1021/acscatal.3c02736
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activation of Molecular Oxygen Toward Producing Hydroxyl Radicals Controllably for Highly Selective Oxidation of Hydroxyl Compounds under Mild Conditions

Xin Liu,
Hong Ma,
Meiyun Zhang
et al.

Abstract: Hydroxyl radicals (OH•), as one of the most highly oxidizing oxidants, are difficult to utilize in chemical synthesis since they usually cause unavoidable oxidative damage with CO2 released. Here, a Co–N–C nanomaterial composed of CoN4 sites on graphitic carbon nitride was constructed, which fulfills the self-cascade activation of O2 in water, wherein OH• is guided to generate in a controlled level and exerts a highly selective oxidation role for efficient synthesis of a variety of organic acids by oxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This indicates that the anchoring of single-atom Co on ZIS facilitates the adsorption, activation, and further reduction of O 2 , and this is consistent with the stronger signals of ROS on Co 1 /ZIS over the pristine ZIS sample in ESR tests (Figure a,b). To further identify whether the single-atom Co on ZIS functions as the active site for photocatalytic selective aerobic oxidation of HMF, the spiking experiment was performed by adding KSCN to deactivate Co sites. As displayed in Figure f, shielding the Co sites significantly decreased the conversion of HMF (one-third of the original value) and the yield of DFF (one-fourth of the original value), verifying the critical role of the Co single atoms on ZIS as active sites in dramatically improving photocatalytic aerobic oxidation of HMF.…”
Section: Resultsmentioning
confidence: 82%
“…This indicates that the anchoring of single-atom Co on ZIS facilitates the adsorption, activation, and further reduction of O 2 , and this is consistent with the stronger signals of ROS on Co 1 /ZIS over the pristine ZIS sample in ESR tests (Figure a,b). To further identify whether the single-atom Co on ZIS functions as the active site for photocatalytic selective aerobic oxidation of HMF, the spiking experiment was performed by adding KSCN to deactivate Co sites. As displayed in Figure f, shielding the Co sites significantly decreased the conversion of HMF (one-third of the original value) and the yield of DFF (one-fourth of the original value), verifying the critical role of the Co single atoms on ZIS as active sites in dramatically improving photocatalytic aerobic oxidation of HMF.…”
Section: Resultsmentioning
confidence: 82%
“…Besides, some studies have also illustrated that the generated superoxide can be converted into H 2 O 2 , which is further decomposed into the hydroxyl radicals as the ROS. 19 Additionally, singlet oxygen and its analogue can also be formed from O 2 as the ROS. 20 These reported results suggest that the ROS can be adjusted by the reaction conditions.…”
Section: Mechanism For the Aerobic Oxidative Transformation Of Hmfmentioning
confidence: 99%
“…However, the contribution of CoN 4 sites in the O-H bond activation and the generated reactive oxygen species needed more work to be clearly illustrated. Moreover, they further developed a Co-N-C carbon material composed of CoN 4 sites using similar methods with some modifications,19 which could catalyze the oxidation of HMF to FDCA even at 25 °C under atmospheric O 2 pressure. They revealed that O 2 was initially activated into superoxide radicals at CoN 4 sites and subsequently converted to H 2 O 2 , which was further converted into OH • at a sufficiently low level by adjusting the pH value of the aqueous solution (Fig.13).…”
mentioning
confidence: 99%